Вещность и вечность - Макарова Елена Григорьевна (Самокат для родителей, 2011)
Экземпляры: аб. (2012) / Инвентарный номер: 54494 / Цена: / Сис.шифр: 74.1 / Авт.знак: М 15 / ГРНТИ: 14.23 / ББК: 74.100.5